The GzMYB-7D1 gene of Guizimai No.1 wheat is essential for seed anthocyanins accumulation and yield regulation. (July 2022) - Luo, Jie; Huang, Weiting; Yan, Jun; Fang, Zhongming; Ren, Mingjian
Abstract: Anthocyanins are antioxidants with important benefits for human health. Therefore, they have caught the interest of plant breeding programs. In this study, GzMYB-7D1, the key gene responsible for anthocyanin synthesis regulation in the purple Guizimai No.1 wheat, was transferred into Zhonghua 11 (ZH11) rice. Compared to wild-type ZH11, anthocyanin accumulated in the seeds of GzMYB-7D1 overexpressing lines. Furthermore, anthocyanin content kept increasing in the growing panicle of GzMYB-7D1 overexpressing lines, accumulating mostly in the rice glumes and grains during maturation, along with a concomitant steady decrease in chlorophyll. Genes related to anthocyanin synthesis, including OsPAL4, Os4CL3, OsCHS, OsDFR, OsANS, and Os3GT, exhibited much higher expression in the panicles of GzMYB-7D1 overexpressing lines than in those of wild-type ZH11. Interestingly, the grain yield per plant was significantly improved in GzMYB-7D1 overexpressing lines, as indicated by a higher tiller number per plant and branching of the secondary panicle, together with a significantly higher content of total amino acids. In conclusion, the GzMYB-7D1 gene of Guizimai No.1 wheat is essential for regulating seed anthocyanin levels and grain yield in rice, and could be applied to attain rice varieties with better nutritional value and improved yields. Highlights: Transgenic rice plants overexpressing GzMYB-7D1 from purple wheat were constructed. GzMYB-7D1 overexpressing lines showed high accumulation of anthocyanins at maturity. Strong expression of DFR and ANS may explain anthocyanin accumulation at maturity. GzMYB-7D1 overexpressing lines attained a high yield. GzMYB-7D1 could substantially augment the nutritional value and yield of rice.